The Correlation between Screen Time, Anxiety, and Sleep Quality Towards Archery Performance of Central Java Student Athletes in 2023 - Faqiha, Farah Yumna; Hartono, Mugiyo; Hanani, Endang Sri; Sumartiningsih, Sri (Journal of Physical Education and Sports, 2023)
In this digital era, excessive screen time usage will cause an issue. Archery requires a high level of concentration and a good state of mind in shooting. Screen time is one of the indicators that affects archers. This study aimed to identify the correlation between screen time, anxiety, and sleep quality towards archery performance. This study used cross-sectional correlation with survey test design. Thirty of the student’s archery athletes were volunteers and signed informed consent to follow the study. The research instrument to measure data used: 1) the Questionnaire for Screen Time of Adolescents (QUEST), 2) the Sport Anxiety Scale (SAS), 3) the Pittsburgh Sleep Quality Index (PSQI), and 4) an archery scoring test. The result showed that no significant correlation between screen time (p = 0.28, r = 0.204 and sleep quality (p = 0.26, r = -0.213) on archery performance (p > 0.05). A significant correlation was found between anxiety and archery performance (p = 0.04, r = - 0.372). The study concluded that the relation of when anxiety increased the performance of archery decreased. Both screen time and sleep quality were low correlations.